2003
DOI: 10.1111/j.1651-2227.2003.tb02519.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic gastric rupture in a 3‐month‐old girl

Abstract: This case reports on idiopathic gastric rupture in a 3‐mo‐old girl who had frequent episodes of vomiting and abdominal distension the day before admission to the clinic. Metabolic acidosis was detected and rotavirus antigen was identified in the stools. Abdominal X‐rays and CT scans revealed free air and fluid in the abdominal cavity, leading to a diagnosis of gastrointestinal perforation. During surgery, idiopathic gastric rupture was detected and treated. The postoperative course was uneventful. Conclusion:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
10
0
4
Order By: Relevance
“…2 Habitualmente, las perforaciones gástricas en adultos son secundarias a úlcera péptica 1 o tumor, 3 mientras que en los neonatos existen factores de riesgo asociados a esta entidad, con asfixia, prematurez, isquemia, ausencia congénita de la musculatura gástrica o aumento de la presión intraluminal. de vía aérea), sonda nasogástrica o ventilación a presión positiva.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…2 Habitualmente, las perforaciones gástricas en adultos son secundarias a úlcera péptica 1 o tumor, 3 mientras que en los neonatos existen factores de riesgo asociados a esta entidad, con asfixia, prematurez, isquemia, ausencia congénita de la musculatura gástrica o aumento de la presión intraluminal. de vía aérea), sonda nasogástrica o ventilación a presión positiva.…”
Section: Discussionunclassified
“…2 En pacientes pediátricos no neonatos se han propuestos diversos factores etiológicos, pero en la mayoría su origen sigue siendo desconocido. Nuestro objetivo es comunicar un caso de ruptura gástrica idiopática en una niña de dos años de edad, donde revisamos signos, síntomas, consideraciones diagnósticas y terapéuticas de esta entidad.…”
Section: Introductionunclassified
“…Although spontaneous gastric rupture in neonates has been proposed to attribute to some factors including congenital absence of gastric musculature, prematurity, ischemia, and increased gastric pressure due to other gastrointestinal lesions or inadequate ventilation [10][11][12], the etiology of this condition in children still remains obscure. It has been reported that overeating or severe vomiting may contribute to increased luminal pressure resulting in idiopathic gastric rupture in children [2,3]. On the other hand, several mechanisms such as blunt abdominal trauma [4][5][6], cardiopulmonary resuscitation [7,8], the Heimlich maneuver [9], and diving [13] are known to directly cause gastric perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric rupture is sometimes seen in the neonatal period, but rarely develops in childhood [1][2][3]. Although spontaneous gastric rupture in neonates has been proposed to attribute to some factors including congenital absence of gastric musculature, prematurity, ischemia, and increased gastric pressure due to other gastrointestinal lesions or inadequate ventilation [10][11][12], the etiology of this condition in children still remains obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation